Problematika Pengajuan PKPU oleh Kreditor Berdasarkan UU No. 37 Tahun 2004 Tentang Kepailitan dan PKPU - Manogihon, Benedictus Hananta; Wiradiputra, Ditha (UNES Law Review, 2023)
Postponement of Debt Payment Obligations is an effort that can be made by the Debtor to avoid bankruptcy. The purpose of this research is to explain the efforts to postpone the payment of debts from a legal perspective and to find out the practice of suspension of obligations for payment of debts in court, especially regarding the submission of applications for suspension of obligations for payment of debts by creditors. The method used is normative juridical. Data obtained through document study. The results of this study are that the considerations of the Panel of Judges in this case are normative and in accordance with the applicable provisions, namely Law number 4 of 1998 covering the reasons for submitting an application for Suspension of Obligations for Debt Payments, filing an application for Suspension of Obligations for Debt Payments in response to a petition for bankruptcy, granting a Suspension of Obligations for Debt Payments Debt Payment Obligations, management fees, and management fees.